ANTIOXIDANT ACTIVITY AND INHIBITORY EFFECT OF SOME COMMONLY USED MEDICINAL PLANTS AGAINST LIPID PER-OXIDATION IN MICE BRAIN - Khan, Asmatullah; Nazar, Halima; Sabir, Syed Mubashar; Irshad, Muhammad; Awan, Shahid Iqbal; Abbas, Rizwan; Akram, Muhammad; Khaliq, Abdul; Texeira Rocha, João Batista; Ahmad, Syed Dilnawaz; Malik, Farnaz (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The present study compares the protective properties of aqueous extracts of six medicinal plants, Phyllanthus emblica, Terminalia chebula (black and yellow), Terminalia arjuna, Balsamodendron Mukul and Alium sativum against lipid per-oxidation in mice brain. Methods: The antioxidant activities were analyzed by lipid per-oxidation assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical assay, total antioxidant activity and metal chelation. Results: The extracts (fruits and bark) showed inhibition against thiobarbituric acid reactive species (TBARS) induced by pro-oxidant (10 µM FeSO4) in mice brain. Moreover, the free radical scavenging activities of the extracts was evaluated by the scavenging of DPPH radical (IC50, 23.23±1.2 µg/ml (Phyllanthus emblica), 20.24±0.9 µg/ml (Terminalia chebula yellow) and 17.33±1.1 µg/ml (Terminalia chebula black), 19.44±0.45 µg/ml (Terminalia arjuna), 56.59±2.1 µg/ml (Balsamodendron Mukul) and ˂ 200 µg/ml (Alium sativum). Conclusion: The higher antioxidant and inhibitory effect of Terminalia chebula black in this study could be attributed to its significantly higher phenolic content, Fe(II) chelating ability, reducing ability and free radical scavenging activity. Therefore oxidative stress in brain could be potentially prevented by the intake of these plants.